Green synthesis of silver/montmorillonite/chitosan bionanocomposites using the UV irradiation method and evaluation of antibacterial activity - Shameli, Kamyar; Ahmad, Mansor; Wan Yunus, Wan Md Zin; Rustaiyan, Abdolhossein; Ibrahim, Nor Azowa; Zargar, Mohsen; Abdollahi, Yadollah (Dove Medical Press, 2010)
In this study, silver nanoparticles (Ag-NPs) were synthesized using a green physical synthetic route into the lamellar space of montmorillonite (MMT)/chitosan (Cts) utilizing the ultraviolet (UV) irradiation reduction method in the absence of any reducing agent or heat treatment. Cts, MMT, and AgNO3 were used as the natural polymeric stabilizer, solid support, and silver precursor, respectively. The properties of Ag/MMT/Cts bionanocomposites (BNCs) were studied as the function of UV irradiation times. UV irradiation disintegrated the Ag-NPs into smaller sizes until a relatively stable size and size distribution were achieved. Meanwhile, the crystalline structure and d-spacing of the MMT interlayer, average size and size distribution, surface morphology, elemental signal peaks, functional groups, and surface plasmon resonance of Ag/MMT/Cts BNCs were determined by powder X-ray diffraction, transmission electron microscopy, scanning electron microscopy, energy dispersive X-ray fluorescence, Fourier transform infrared, and UV-visible spectroscopy. The antibacterial activity of Ag-NPs in MMT/Cts was investigated against Gram-positive bacteria, ie, Staphylococcus aureus and methicillin-resistant S. aureus and Gram-negative bacteria (ie, Escherichia coli) by the disk diffusion method on Muller–Hinton Agar at different sizes of Ag-NPs. All of the synthesized Ag/MMT/Cts BNCs were found to have high antibacterial activity. These results show that Ag/MMT/Cts BNCs can be useful in different biologic research and biomedical applications, such as surgical devices and drug delivery vehicles.